Experimental study on the effects of injection timing using reuse of waste energy as a fuel on a diesel engine - Dvsrbm Subrahmanyam; Manikandan Jegathesan (International Journal of Reconfigurable and Embedded Systems (IJRES), 2023)
In the course of this study, an eco-friendly alternative fuel was manufactured by transesterifying waste oils with the help of alcohol and a catalyst. As required by the American society for testing and materials (ASTM) requirements, we conducted an analysis on the acquired waste cooking oil biofuel (WOB) to determine its most important properties. We were successful in producing three separate fuel mixes, which we will refer to as BF100WOB0 (100% diesel), BF80WOB20 (80% diesel and 20% biofuel), and BF0WOB100 (100% biofuel) respectively. This research used a diesel engine with direct injection; the engine had a single cylinder, and the computer that operated it was located in the cabin. The results showed that the BF80WOB20 had a 3.8% increase in fuel consumption and a 1.4% loss in thermal efficiency while it was at a temperature of 26.5Â° b top dead center (TDC) conditions with low injection time led to decreased levels of both nitrogen oxides (NOx) and hartridge smoke level (HSL) emissions. The addition of 20% WOB to the fundamental fuel improved the engine combustion characteristics at 26.5Â° b TDC. This improvement occurred at the same time.